2020
DOI: 10.3389/fpsyt.2020.580103
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Determinants Among a Psychiatric Outpatient Sample of Vietnamese Migrants in Germany

Abstract: Background: Mental health risk-factors for Asian migrants have been studied almost exclusively in the US, Canada, and Australia but not in European countries. Therefore, we aimed to identify sociodemographic, clinical, and migration-surrounding factors associated with experienced mental distress among Vietnamese migrants in Germany.Method: 305 Vietnamese migrants utilizing Germany's first Vietnamese psychiatric outpatient clinic filled out at admission the Brief-Symptom-Inventory 18 (BSI-18) as well as a quest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In studies from different countries all over the world it is shown that discrimination can lead to poorer mental health in immigrants [ 21 , 26 , 33 37 ]. In line with findings on the role of lower socioeconomic status on mental health of non-migrants, this factor also seems to negatively influence the mental health of immigrants [ 34 ].…”
Section: Introductionsupporting
confidence: 85%
“…In studies from different countries all over the world it is shown that discrimination can lead to poorer mental health in immigrants [ 21 , 26 , 33 37 ]. In line with findings on the role of lower socioeconomic status on mental health of non-migrants, this factor also seems to negatively influence the mental health of immigrants [ 34 ].…”
Section: Introductionsupporting
confidence: 85%
“…Previous studies noted poor mental health of unemployed migrants living in Western countries. This includes Turkish migrants in the Netherlands ( Bengi-Arslan et al, 2002 ), Southeast Asians in Canada ( Beiser and Hou, 2001 ; Beiser and Hou, 2006 ), Somali refugees in London ( Warfa et al, 2012 ), South Asians in Canada ( Dean and Wilson, 2009 ), Vietnamese migrants in Germany ( Wolf et al, 2020 ), Asian Americans ( John et al, 2012 ), Kurdish migrants in Finland ( Rask et al, 2016 ), African refugees in the United States ( Abdelkerim and Grace, 2012 ) and Indian and Chinese migrants in New Zealand ( Pernice et al, 2009 ). Previous evidence has highlighted how unemployment affects the mental health of immigrant men, especially those from ethnic minorities, and has revealed that these effects differ from those observed in host populations.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the most common symptoms experienced by unemployed Asian men ( Beiser et al, 1993 ; Bengi-Arslan et al, 2002 ; Disney, 2021 ; John et al, 2012 ; Warfa et al, 2012 ; Wolf et al, 2020 ). In some Western countries, unemployed migrant men from ethnic minority countries are more likely to report generalised anxiety disorder (GAD) ( Disney, 2021 ), hopelessness, social dysfunction, somatic symptoms ( Bengi-Arslan et al, 2002 ), PTSD ( Disney, 2021 ) in response to lengthy job searches and inability to find employment in their relevant skill set ( Axelsson, 2017 ; Dean and Wilson, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that implementing a clinical utilization and non-utilization recruitment strategy introduced heterogeneity in the sample, particularly in terms of variations in depressive symptoms, among the two recruitment pathways. The decision to include clinical utilization as well as non-utilization participants was made to obtain a more naturalistic sample, considering previous research that postulated an under or delayed utilization of professional healthcare services among Vietnamese migrants in Germany ( Ta et al, 2014 ; Wolf et al, 2020 ). Nevertheless, the possibility of biases because of the two-pathway recruitment strategy cannot be entirely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Vietnamese represent Germany’s largest Southeast Asian migrant population, with a population of 185,000 ( Destatis, 2020 ). Despite the relatively large number of Vietnamese migrants in Germany, research on this minority group remains scarce ( Kim et al, 2012 ; Nguyen et al, 2021 ; Ta et al, 2014 ; Wolf et al, 2020 ). Depression was found to be the most common diagnosis among Vietnamese migrants in Germany ( Ta et al, 2014 ), with higher ( Merbach et al, 2008 ) to similar ( Hahn et al, 2016 ) levels of depressive symptoms among first-generation Vietnamese migrants compared to the native population born in Germany.…”
Section: Vietnamese Migrants In Germanymentioning
confidence: 99%